2021
DOI: 10.17559/tv-20190522104029
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Surface Roughness and Power in Turning Process Using Response Surface Method and ANN

Abstract: This paper examines the influence of three cutting parameters (cutting speed, cutting depth and feed rate) on surface roughness and power in the longitudinal turning process of aluminium alloy. For the analysis of data gathered by experiments, two methods for prediction of responses were employed, namely Response Surface Methodology (RSM) and Artificial Neural Network (ANN). The research has shown that the ANN gives a better prediction of surface roughness than the RSM. In the modelling of the power, the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…One of the most common ways of doing this is to reduce storage capacity. Therefore, this paper considers three constraints in the model, including the supplier's minimum order quantity setting, inventory constraints and purchasing demand constraints [33]. Finally, an improved genetic algorithm is proposed to find the optimal purchasing volume and allocation scheme.…”
Section: The Framework Of Centralized Procurement Modelmentioning
confidence: 99%
“…One of the most common ways of doing this is to reduce storage capacity. Therefore, this paper considers three constraints in the model, including the supplier's minimum order quantity setting, inventory constraints and purchasing demand constraints [33]. Finally, an improved genetic algorithm is proposed to find the optimal purchasing volume and allocation scheme.…”
Section: The Framework Of Centralized Procurement Modelmentioning
confidence: 99%
“…The outcomes revealed that a higher V caused a decreased SR and stable machining. Aljinović et al examined the impacts of the V, f, and D on the SR and power consumed (PC) of the turning aluminium alloy using the RSM and ANN [15]. The authors stated that the ANN provided a better accuracy for the responses, as compared to the RSM one.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive accuracy of data-driven model is generally better than that of the theoretical model. The data-driven modeling method for surface roughness prediction mainly includes multiple regression modeling method [17,18], response surface methodology (RSM) [19][20][21] and intelligence algorithm modeling method (such as neural network [22][23][24][25] and support vector machine (SVM) [26][27][28]). However, since the data-driven model is based on data, and the more data is, the higher the accuracy of the model is, so it needs to spend the large experimental cost.…”
Section: Introductionmentioning
confidence: 99%